High temperature oxidation of T91 alloy of steam reformer - Rosdin, Muhammad Rafiq Haikal; Ismail, Ahmad Abdul Mun'im; Abdul Hamid, Abd. Malek; Purwanto, Hadi; Illias, Suhaimi; Syed Abu Bakar, Syed Noh; Ani, Mohd Hanafi (Springer, 2022)
Steam plays a significant role in the reforming process of hydrogen. It is generated in a waste heat recovery unit at temperature of 650 °C. Along with the high operating temperature, the situation promotes acceleration of high temper- ature oxidation. This will cause fouling and spalling of oxide scales at the boiler tube. Eventually, fouling will reduce heat transfer between the tube and steam gener- ated, causing a higher temperature is needed to produce steam. Until now, the only approach used by the industry is to manually replace the corroded boiler tube. Other than that, many studies have been conducted on the behavior of boiler tubes at temper- atures exceeding 800 °C. However, to our knowledge, no “in-situ” study has been done to investigate the high temperature electrochemistry aspect of boiler tubes. A review conducted by B.A Pint [1] in his paper mentioned that it is notoriously diffi- cult to imitate the harsh environments in laboratory scale. Popov [2] stated that the only available method to decrease corrosion rate at high temperature corrosion and hot corrosion is only by implementing protective coatings. This project was carried out to investigate the corrosion potential of T91 boiler tube at 650 °C for 30 min, 1 h, 2 h, 8 h, and 12 h, measure the current density (I corr ) by calculating corrosion poten- tial (Ecorr ) value using Tafel Extrapolation and determine the current conductivity of oxygen gas at 650 °C. Apart from that, the oxide layer thickness at exposed temper- ature is also determined to measure the oxidation kinetics. The study concludes that there was an increase of 8.49% in current conductivity between the blank experiment and T91 alloy conductivity test. The oxide layer formed on the sample is significant to calculate the oxidation kinetics of the sample using parabolic rate constant (Kp), resulting with the value of 6.78 × 10–14 m2s−1.